Hydrogen adsorption catalyst and preparation method thereof

By introducing yttrium and transition metals into the hydrogenation reaction catalyst, designing a heterogeneous structure, and using liquid phase method and dual template technology to construct a high specific surface area carrier, the problem of hydrogen adsorption and insufficient catalytic activity of the catalyst in an acidic environment was solved. A significant improvement in catalyst performance was achieved.

CN119340411APending Publication Date: 2025-01-21WUHAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411445072.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing hydrogen adsorption capacity and hydrogen oxidation catalytic activity of existing hydroxide reaction catalysts in acidic environments are insufficient, making it difficult to effectively catalyze low concentrations or impurities-containing hydrogen gas, limiting the high-performance applications of hydrogen fuel cells and hydrogen sensors.

Method used

By introducing the rare earth element yttrium and specific transition metals, designing heterostructures, and using a one-step liquid phase method combined with physical and chemical dual template technology, a high specific surface area carrier with a continuous microporous-mesoporous structure is constructed to improve the dispersion of platinum particles. and electrochemically active area.

Benefits of technology

It significantly enhances the hydrogen adsorption capacity and hydrogen oxidation catalytic activity of the catalyst in acidic environments, improves the rapid diffusion and adsorption efficiency of hydrogen, enhances the overall performance and stability of the catalyst, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340411A_ABST
    Figure CN119340411A_ABST
Patent Text Reader

Abstract

The invention provides a hydrogen adsorption catalyst and a preparation method thereof. The catalyst is prepared by the following steps: S1, preparing a polymer solution under a stirring condition, and then sequentially adding a yttrium precursor solution and a transition metal precursor solution to prepare a mixed solution; s2, preparing dispersion liquid containing zinc oxide, adding the dispersion liquid into the mixed solution, and performing ultrasonic treatment, stirring and freeze drying to obtain a sample; s3, under the protection of inert gas, heating the sample, preserving heat, and naturally cooling to obtain a porous carrier; and S4, grinding the porous carrier, putting the porous carrier into a solvent, adding a platinum precursor solution, drying under the protection of inert gas, carrying out heat treatment under specific gas, naturally cooling, and grinding to obtain the hydrogen adsorption catalyst. The rare earth yttrium and transition metal heterostructure designed by the invention synergistically constructs a continuous micropore-mesopore high-specific-surface-area carrier with a rapid hydrogen diffusion characteristic, and the prepared material is higher in platinum dispersity, large in electrochemical active area and high in hydrogen oxidation catalytic capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of hydrogen energy technology, and in particular to a hydrogen absorption catalyst and a preparation method thereof. Background Art

[0002] The hydrogen oxidation reaction is an electrode reaction in which hydrogen loses electrons and converts to protons on the electrode surface. It has the characteristics of fast reaction and low overpotential, and plays a vital role in electrochemical energy conversion devices. Usually, the hydrogen oxidation reaction can be combined with a series of reactions such as oxygen reduction, hydrogen reduction, and carbon dioxide reduction to form devices with different functions. This process is not only closely related to the energy conversion efficiency of hydrogen fuel cells, but also indispensable for the construction of efficient and fast-responding electrochemical hydrogen sensors. When the hydrogen oxidation reaction is coupled with the oxygen reduction reaction, it can form a hydrogen fuel cell, which is currently of great concern in the field of clean energy and an important part of my country's energy strategy. As a new secondary energy technology, fuel cells have the advantages of high energy conversion efficiency, fast response and no pollution. However, due to cost issues and constraints on key catalyst materials, the promotion of its large-scale application is greatly limited. In addition, the coupling of these two reactions can also be used as an advanced electrochemical hydrogen sensor. Compared with other types of sensors, it can sense hydrogen leaked into the environment more quickly, providing protection for safe operations in hydrogen-related scenarios.

[0003] However, in order to effectively sense leaks within a certain range, hydrogen sensors are generally placed above the space. The leaked hydrogen that diffuses to the sensor is generally of very low concentration, and it takes a certain amount of time to be effectively detected. At the same time, current fuel cell devices can basically only use very pure hydrogen, and the hydrogen purification process accounts for a certain proportion of the cost. Therefore, developing new catalysts with rapid hydrogen adsorption and transfer, and improving their catalytic ability for low-concentration hydrogen or even impure hydrogen, is a key issue faced in the development of a new generation of high-performance hydrogen sensors and fuel cells.

[0004] At present, the hydrogen oxidation reaction catalyst used in commercial scenarios is a granular supported platinum-carbon material with a relatively simple structure and great room for improvement. Researchers have done a lot of work on optimizing the catalyst structure. For example, patent CN111554946B discloses a platinum alloy catalyst with high hydrogen oxidation catalytic activity. The amount of platinum in the anode catalyst of the fuel cell is reduced by introducing elements such as gold and silver to form alloys with platinum while maintaining the original activity. For example, patent CN114678551A discloses a rare earth element modified platinum ruthenium nanoparticle, and a rare earth modified platinum ruthenium catalyst is prepared by liquid phase mixing and subsequent two-step heat treatment, which improves the catalyst's hydrogen oxidation reaction catalytic activity in alkaline. Patent CN117976925A also discloses a palladium nickel @ carbon composite catalyst prepared by introducing transition metal nickel, which has excellent activity and stability in alkaline hydrogen oxidation reactions. Patent CN115872355B discloses a mesoporous hydrogen storage and hydrogen oxidation catalyst material modified with phosphorus, nitrogen and boron and doped with palladium and carbon. The finely designed pore structure and electronic structure control improve the hydrogen storage and hydrogen oxidation capacity of the catalyst. In summary, the existing technology usually uses pore structure design, doping, introduction of transition metals, etc. to improve the hydrogen oxidation catalytic ability of platinum catalysts. The methods are relatively simple and the improvement effect is limited. In addition, many studies on hydrogen oxidation catalysts are concentrated under alkaline conditions.

[0005] Therefore, it is urgent to study a new type of catalyst composition and structure and develop a new method for preparing multi-functional materials to synergistically improve the hydrogen adsorption capacity and hydrogen oxidation catalytic activity of the catalyst in an acidic environment. Summary of the invention

[0006] In view of this, the present invention proposes a hydrogen adsorption catalyst and a preparation method thereof. The catalyst introduces rare earth element yttrium and a specific transition metal, and designs a unique heterostructure by utilizing the electrostatic interaction between them. During the preparation process, we further adopted a one-step liquid phase method, cleverly combining physical and chemical dual template technology, and successfully constructed a high specific surface area carrier with a continuous microporous-mesoporous structure to facilitate the rapid diffusion of hydrogen. The resulting catalyst material not only has highly dispersed platinum particles, but also has a large electrochemical active area and excellent hydrogen oxidation catalytic performance.

[0007] In a first aspect, the present invention provides a method for preparing a hydrogen adsorption catalyst, the method comprising the following steps:

[0008] S1. Under stirring conditions, preparing a polymer solution, and then sequentially adding an yttrium precursor solution and a transition metal precursor solution to obtain a mixed solution;

[0009] S2, preparing a dispersion containing zinc oxide, adding the dispersion to the mixed solution of step S1, ultrasonically stirring until uniform dispersion, and freeze-drying to obtain a sample;

[0010] S3, under the protection of an inert gas, heating the sample of step S2 and keeping it warm, and then naturally cooling it to room temperature to obtain a porous carrier;

[0011] S4, grinding the porous carrier of step S3 and placing it in a solvent, adding a platinum precursor solution, drying it under the protection of an inert gas, and then heat treating it under a specific gas, and grinding it after natural cooling to obtain a hydrogen adsorption catalyst.

[0012] By adopting the above technical solution, the synergistic effect of yttrium and transition metal enhances the hydrogen adsorption capacity and hydrogen oxidation catalytic activity of the catalyst in an acidic environment; and the dispersibility of platinum is significantly improved, increasing the effective active sites of the catalyst. The hydrogen adsorption catalyst prepared by this method not only has a porous structure with a high specific surface area, promotes the rapid diffusion of hydrogen, and improves the overall performance of the catalyst; it also simplifies the preparation process, reduces production costs, and is conducive to large-scale industrial production.

[0013] Furthermore, in step S1, in the polymer solution, the polymer is selected from one or more of polyethylene glycol, polyvinyl pyrrolidone, polyacrylonitrile, polyimide, polyvinylidene fluoride or polyurethane; the solvent is selected from one or more of water, isopropanol, ethanol, acetone, dimethylformamide or N-methylpyrrolidone; and the concentration of the polymer solution is 0.1 to 1 g / ml.

[0014] The polymer has good solubility and stable chemical properties, which helps to form a uniform mixed solution; the solvent can effectively dissolve the polymer and promote the uniform dispersion of the precursor. By adopting the above technical solution, the type and concentration of the polymer can be accurately controlled, and the pore size distribution and specific surface area of ​​the catalyst carrier can be adjusted, thereby optimizing the adsorption and diffusion properties of hydrogen. The selection of a suitable solvent helps to evenly disperse the precursor, avoid uneven deposition caused by excessive local concentration, and thus improve the dispersibility of platinum.

[0015] Further, the yttrium precursor is selected from one or more of yttrium bromide, yttrium chloride, yttrium nitrate, yttrium acetate, yttrium sulfate or yttrium acetylacetonate; the concentration of the yttrium precursor solution is 0.01-0.5 mol / L;

[0016] In the transition metal precursor, the cation is sodium or potassium, and the anion is selected from one or more of ferrite, tetracarbonylferrite, cobalt cyanate, cobaltate, tetracarbonylcobaltate or nickel cyanate; the concentration of the transition metal precursor solution is 0.01-0.5 mol / L.

[0017] The yttrium precursor is easy to dissociate in the solution to form a uniform yttrium precursor solution with a concentration range of 0.01 to 0.5 mol / L, which is conducive to the uniform distribution of the yttrium element in the catalyst, thereby enhancing the structural stability and catalytic activity of the catalyst; the transition metal precursor has good solubility and stability in the solution, and the concentration is set in the range of 0.01 to 0.5 mol / L, ensuring that the transition metal ions can be evenly incorporated into the catalyst structure, enhancing the catalyst's hydrogen adsorption capacity and hydrogen oxidation reaction activity under acidic conditions. By adopting the above technical solution, not only can the durability and activity of the catalyst be enhanced, but also its catalytic efficiency under acidic conditions can be improved.

[0018] Furthermore, in step S1, the mass ratio of the yttrium element in the yttrium precursor, the transition metal cation and the polymer is 1:(0.2-5):(10-1000).

[0019] By adopting the above technical solution, not only the uniform distribution of the rare earth element yttrium and the transition metal in the catalyst is ensured, but also the polymer matrix can effectively support and stabilize these active components.

[0020] Furthermore, in step S2, the particle size of the zinc oxide is 20-100 nm; and the mass ratio of the zinc oxide to the polymer is 1:(10-50).

[0021] By adopting the above technical solution, the particle size of zinc oxide is set in the range of 20 to 100 nm. Such nano-scale size can provide a larger specific surface area and increase the number of active sites, thereby improving the activity of the catalyst and the adsorption efficiency of hydrogen. At the same time, the mass ratio of zinc oxide to polymer is set to 1: (10 to 50). This ratio can ensure that the zinc oxide particles are evenly dispersed in the polymer matrix, forming a high specific surface area carrier with a continuous microporous-mesoporous structure, which is conducive to the rapid diffusion of hydrogen.

[0022] Furthermore, the inert gas is selected from argon or nitrogen, and the gas flow rate is 10 to 200 ml / min.

[0023] By adopting the above technical solution, sufficient gas flow can be provided to carry away the volatile substances generated by the reaction, while excessively high flow rate can be avoided to cause material loss or affect the uniformity of the reaction.

[0024] Furthermore, in step S3, the heating method is: heating to 200-900°C at a rate of 1-10°C / min.

[0025] By adopting the above technical solution, it is possible to ensure a smooth temperature change and avoid internal stress concentration or structural damage of the material caused by sudden temperature changes, thereby improving the structural stability and catalytic activity of the catalyst.

[0026] Furthermore, in step S4, the platinum precursor is selected from one of platinum nitrate, platinum perchlorate or platinum acetylacetonate; the concentration of the platinum precursor solution is 0.1-5 g / L; and the mass ratio of the platinum element in the platinum precursor to the polymer is 1:(10-500).

[0027] By adopting the above technical solution, firstly, the platinum precursor has good solubility and stability, and is easy to be evenly dispersed in subsequent steps. Secondly, the concentration of the platinum precursor solution is set in the range of 0.1 to 5 g / L, which ensures the uniform loading of platinum and avoids uneven distribution caused by excessively high or low concentrations. Finally, the mass ratio of platinum element to polymer in the platinum precursor is 1: (10 to 500), which can ensure the uniform dispersion of platinum particles on the carrier, forming a catalyst with high dispersibility and large electrochemical active area.

[0028] Furthermore, in step S4, the specific gas is hydrogen and / or argon, and the gas flow rate is 10-50 mL / min; the heat treatment method is: heating to 200-900° C. at a rate of 1-5° C. / min and keeping warm.

[0029] By adopting the above technical scheme, firstly, the specific gases selected by the present invention have good chemical inertness or reducing properties, and can provide a protective or reducing atmosphere to prevent the catalyst from oxidizing at high temperatures. At the same time, hydrogen also helps to remove residual organic matter and purify the catalyst surface. Secondly, the gas flow rate is set within the range of 10 to 50 mL / min. This flow rate can not only ensure that the gas covers the catalyst surface and promotes uniform heat treatment, but also avoid excessive flow rate to take away catalyst particles or cause waste. Finally, the use of a gradual heating method can ensure that the temperature rises evenly and avoid damage to the catalyst structure caused by the temperature gradient. At the same time, the heat preservation treatment is also conducive to the optimization and stabilization of the internal structure of the catalyst.

[0030] In a second aspect, the present invention relates to a hydrogen adsorption catalyst prepared by the above method, wherein the specific surface area of ​​the hydrogen adsorption catalyst is 400m 2 / g, and the kinetic current density at 0.1V vs.RHE exceeds 5A / mg.

[0031] By adopting the above technical solution,

[0032] The hydrogen adsorption catalyst provided by the present invention has the following beneficial effects compared with the prior art:

[0033] (1) The present invention designs a rare earth yttrium and transition metal heterostructure, and synergistically constructs a continuous microporous-mesoporous high specific surface area carrier with hydrogen rapid diffusion characteristics. The prepared material has higher platinum dispersion, large electrochemical active area, and strong hydrogen oxidation catalytic ability.

[0034] (2) The present invention can form a porous structure with a high specific surface area by introducing yttrium precursor and transition metal precursor and optimizing their mass ratio with the polymer, which significantly enhances the hydrogen adsorption capacity. At the same time, the presence of yttrium element and transition metal helps to form a heterojunction, further improving the hydrogen adsorption efficiency of the catalyst. The selection of platinum precursor and its mass ratio with the polymer are optimized to ensure the uniform dispersion of platinum particles on the catalyst carrier, increase the electrochemical active area, and improve the activity and stability of the catalyst. In addition, the synergistic effect of platinum, yttrium and transition metal enhances the hydrogen oxidation catalytic activity of the catalyst in an acidic environment, which is beneficial for it to show higher activity, stability and reliability in applications such as hydrogen fuel cells and hydrogen sensors.

[0035] (3) The present invention prepares a catalyst carrier with a continuous microporous-mesoporous structure by using zinc oxide nanoparticles, which facilitates the rapid diffusion of hydrogen, thereby achieving rapid adsorption and detection.

[0036] (4) The present invention prepares the catalyst by a one-step liquid phase method, which simplifies the preparation process, reduces energy consumption and cost, and is conducive to large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 This is a SEM morphology image of the hydrogen adsorption catalyst carrier prepared in Example 1 of the present invention;

[0039] Figure 2 The nitrogen absorption-desorption diagram and pore size distribution diagram of the hydrogen absorption catalyst prepared in Example 1 of the present invention, in which the small diagram shown inside is the pore size distribution diagram, and the large diagram shown outside is the nitrogen absorption-desorption diagram;

[0040] Figure 3 The figure is a performance comparison chart of the hydrogen absorption catalysts prepared in Example 1 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of the materials mainly involved in the examples are shown in Table 1 below, and the remaining materials not shown are conventional commercial products.

[0043] Table 1 Material source description

[0044] Serial number Material / Equipment Name Specifications / Models factory 1 Zinc Oxide 10-100nm Macklin

[0045] The following are specific embodiments of the present invention.

[0046] Example 1

[0047] S1. Dissolve polyethylene glycol in water and stir for 6 hours to form a 0.1 g / mL polymer solution; then add 0.01 mol / L yttrium bromide solution and sodium ferrite solution in sequence, set the mass ratio of yttrium element, transition metal element and polymer to 1:0.2:10, and stir for 2 hours to obtain a mixed solution;

[0048] S2, dispersing zinc oxide nanoparticles with a size of 20 nm in a water solvent to prepare a dispersion, setting the mass ratio of zinc oxide to polymer to be 1:10, and adding the dispersion to the mixed solution of step S1, ultrasonicating with a 50W, 40kHz ultrasonic machine, stirring for 1 hour; then placing in a freeze dryer for freeze drying to obtain a sample;

[0049] S3, putting the sample of step S2 into a quartz boat and placing it into an atmosphere furnace, heating the temperature to 900°C at a rate of 1°C / min under the protection of argon gas with a flow rate of 10 mL / min and keeping the temperature for 1 hour, then naturally cooling to room temperature and taking it out to obtain a porous carrier containing a reinforcement phase;

[0050] S4, physically grinding the porous carrier of step S3 and dispersing it in water, adding 0.1 g / L platinum nitrate solution with a mass ratio of platinum to polymer of 1:10, making the two fully contact under nitrogen protection and drying at 40°C; then, heating the temperature to 200°C at a rate of 1°C / min and keeping it warm for 0.5h under a flow rate of 10 mL / min hydrogen / argon mixed gas for secondary heat treatment, naturally cooling to room temperature, taking out and fully physically grinding to obtain a hydrogen adsorption catalyst.

[0051] By testing the porous carrier in step S3, the following is obtained: Figure 1The SEM morphology shown in the figure shows that the catalyst material presents a connected porous structure.

[0052] The catalyst was tested by BET. Figure 2 The nitrogen absorption-desorption diagram shown in the figure, combined with the internal pore size distribution diagram, shows that the catalyst prepared in this embodiment exhibits a microporous and mesoporous composite structure, which is conducive to the rapid transfer of hydrogen inside the catalyst. The specific surface area of ​​the catalyst is 990m 2 / g, and the most probable pore size is 50nm.

[0053] Tested by an electrochemical workstation and a rotating disk electrode, the kinetic current density of the catalyst sample at 0.1 V vs. RHE was 10.5 A / mg.

[0054] Example 2

[0055] S1. Dissolve the polyurethane in N-methylpyrrolidone and stir for 12 hours to form a 1 g / mL polymer solution; then add 0.5 mol / L yttrium acetylacetonate solution and potassium tetracyanonicbonate solution in sequence, set the mass ratio of yttrium element, transition metal element and polymer to 1:5:1000, and stir for 4 hours to obtain a mixed solution;

[0056] S2, dispersing zinc oxide nanoparticles with a size of 100 nm in a water solvent to prepare a dispersion, setting the mass ratio of zinc oxide to polymer to be 1:50, and adding the dispersion to the mixed solution of step S1, continuing ultrasonication and stirring for 2 hours; then putting it into a freeze dryer for freeze drying to obtain a sample;

[0057] S3. Place the sample of step S2 into a quartz boat and place it in an atmosphere furnace. Under the protection of a nitrogen gas with a flow rate of 200 mL / min, heat the temperature to 1500°C at a rate of 10°C / min and keep it warm for 3 hours. Naturally cool it to room temperature and take it out to obtain a porous carrier containing a reinforcement phase.

[0058] S4, physically grinding the porous carrier of step S3 and dispersing it in water, adding 5 g / L acetylacetonate platinum solution with a mass ratio of platinum to polymer of 1:500, making the two fully contact under nitrogen protection and drying at 80°C; then heating to 900°C at a heating rate of 5°C / min under argon with a flow rate of 50 mL / min and keeping warm for 2 hours for secondary heat treatment, naturally cooling to room temperature, taking out and fully physically grinding to obtain a hydrogen adsorption catalyst.

[0059] The BET test of the catalyst showed that the specific surface area of ​​the catalyst prepared in this embodiment reached 428 m 2 / g, tested by electrochemical workstation and rotating disk electrode, the kinetic current density of the catalyst sample at 0.1V vs.RHE is 5.8A / mg.

[0060] Example 3

[0061] S1. Dissolve polyethylene glycol in water and stir for 12 hours to form a 1 g / mL polymer solution; then add 0.5 mol / L yttrium bromide solution and sodium ferrite solution in sequence, set the mass ratio of yttrium element and transition metal element to polymer to 1:5:1000, and stir for 4 hours to obtain a mixed solution;

[0062] S2, dispersing zinc oxide nanoparticles with a size of 100 nm in a water solvent to prepare a dispersion, setting the mass ratio of zinc oxide to polymer to be 1:50, and adding the dispersion to the mixed solution of step S1, continuing ultrasonication and stirring for 2 hours; then putting it into a freeze dryer for freeze drying to obtain a sample;

[0063] S3, putting the sample of step S2 into a quartz boat and placing it in an atmosphere furnace, heating it to 1500°C at a rate of 10°C / min under the protection of nitrogen with a flow rate of 200mL / min and keeping it warm for 3h, cooling it naturally to room temperature and taking it out to obtain a porous carrier containing a reinforcement phase;

[0064] S4, physically grinding the porous carrier of step S3 and dispersing it in water, adding 5g / L platinum nitrate solution with a mass ratio of platinum to polymer of 1:500, making the two fully contact under nitrogen protection and drying at 80°C; then heating to 900°C at a heating rate of 5°C / min under a flow rate of 50mL / min hydrogen / argon mixed gas and keeping warm for 2h for secondary heat treatment, naturally cooling to room temperature, taking out and fully physically grinding to obtain a hydrogen adsorption catalyst.

[0065] The BET test of the catalyst showed that the specific surface area of ​​the catalyst prepared in this embodiment reached 568 m 2 / g, tested by electrochemical workstation and rotating disk electrode, the kinetic current density of the catalyst sample at 0.1V vs.RHE is 7.2A / mg.

[0066] Example 4

[0067] S1. Dissolve the polyurethane in N-methylpyrrolidone and stir for 6 hours to form a 0.1 g / mL polymer solution; then add 0.01 mol / L yttrium acetylacetonate solution and potassium tetracyanonicbonate solution in sequence, set the mass ratio of yttrium element and transition metal element to polymer to 1:0.2:10, and stir for 2 hours to obtain a mixed solution;

[0068] S2, dispersing zinc oxide nanoparticles with a size of 20 nm in a water solvent to prepare a dispersion, setting the mass ratio of zinc oxide to polymer to be 1:10, and adding the dispersion to the mixed solution in step S1, continuing ultrasonication and stirring for 1 hour; then putting it into a freeze dryer for freeze drying to obtain a sample;

[0069] S3, putting the sample of step S2 into a quartz boat and placing it in an atmosphere furnace, heating it to 900°C at a rate of 1°C / min under the protection of argon gas with a flow rate of 10 mL / min and keeping it warm for 1 hour, cooling it naturally to room temperature and taking it out to obtain a porous carrier containing a reinforcement phase;

[0070] S4, physically grinding the porous carrier of step S3 and dispersing it in water, adding 0.1 g / L acetylacetonate platinum solution with a mass ratio of platinum to polymer of 1:10, fully contacting under nitrogen protection and drying at 40°C; then heating to 200°C at a heating rate of 1°C / min under argon with a flow rate of 10 mL / min and keeping warm for 0.5 h for secondary heat treatment, naturally cooling to room temperature, taking out and fully physically grinding to obtain a hydrogen adsorption catalyst.

[0071] Through BET test on the catalyst, the specific surface area of ​​the catalyst prepared in this embodiment is 873m 2 / g, tested by electrochemical workstation and rotating disk electrode, the kinetic current density of the catalyst sample at 0.1V vs.RHE is 9.2A / mg.

[0072] Example 5

[0073] S1. Dissolve polyvinyl pyrrolidone in water and stir for 8 hours to form a 0.2 g / mL polymer solution; then add 0.05 mol / L yttrium solution (the molar ratio of yttrium nitrate to yttrium sulfate is 1:1) and disodium tetracarbonyl ferrate solution in sequence, set the mass ratio of yttrium element and transition metal element to polymer to 1:1:100, and stir for 2 hours to obtain a mixed solution;

[0074] S2, dispersing zinc oxide nanoparticles with a size of 50 nm in a water solvent to prepare a dispersion, setting the mass ratio of zinc oxide to polymer to be 1:20, and adding the dispersion to the mixed solution in step S1, continuing ultrasonication and stirring for 1.5 hours; then placing in a freeze dryer for freeze drying to obtain a sample;

[0075] S3, putting the sample of step S2 into a quartz boat and placing it into an atmosphere furnace, heating the temperature to 1200°C at a rate of 5°C / min under the protection of nitrogen with a flow rate of 50 mL / min and keeping the temperature for 2 hours, cooling naturally to room temperature and taking it out to obtain a porous carrier containing a reinforcement phase;

[0076] S4, physically grinding the porous carrier of step S3 and dispersing it in water, adding 1 g / L platinum perchlorate solution with a mass ratio of platinum to polymer of 1:50, fully contacting under nitrogen protection and drying at 60°C; then heating to 800°C at a heating rate of 2°C / min under a flow rate of 20 mL / min hydrogen and keeping the temperature for 1 hour for secondary heat treatment, naturally cooling to room temperature, taking out and fully physically grinding to obtain a hydrogen adsorption catalyst.

[0077] The BET test of the catalyst showed that the specific surface area of ​​the catalyst prepared in this embodiment reached 694 m 2 / g, tested by electrochemical workstation and rotating disk electrode, the kinetic current density of the catalyst sample at 0.1V vs.RHE is 8.5A / mg.

[0078] Example 6

[0079] S1. Dissolve polyvinylidene fluoride in dimethylformamide and stir for 10 hours to form a 0.2 g / mL polymer solution; then add 0.2 mol / L yttrium acetate solution and cobalt (the molar ratio of potassium tetracarbonyl cobaltate to yttrium nitrate is 1:1) in sequence, set the mass ratio of yttrium element and transition metal element to polymer to 1:2:200, and stir for 2 hours to obtain a mixed solution;

[0080] S2, dispersing zinc oxide nanoparticles with a size of 30 nm in a water solvent to prepare a dispersion, setting the mass ratio of zinc oxide to polymer to be 1:40, and adding the dispersion to the mixed solution in step S1, continuing ultrasonication and stirring for 1 hour; then placing in a freeze dryer for freeze drying to obtain a sample;

[0081] S3, putting the sample of step S2 into a quartz boat and placing it in an atmosphere furnace, heating it to 1000°C at a rate of 2°C / min under the protection of argon gas with a flow rate of 20 mL / min and keeping it warm for 2.5 hours, cooling it naturally to room temperature and taking it out to obtain a porous carrier containing a reinforcement phase;

[0082] S4, physically grinding the porous carrier of step S3 and dispersing it in water, adding 0.4 g / L acetylacetonate platinum solution with a mass ratio of platinum to polymer of 1:30, fully contacting under nitrogen protection and drying at 50°C; then heating to 300°C at a heating rate of 3°C / min under a hydrogen / argon mixed gas flow rate of 20 mL / min and keeping warm for 1.5 hours for secondary heat treatment, naturally cooling to room temperature, taking out and fully physically grinding to obtain a hydrogen adsorption catalyst.

[0083] The BET test of the catalyst showed that the specific surface area of ​​the catalyst prepared in this embodiment was 590 m 2 / g, tested by an electrochemical workstation and a rotating disk electrode, the kinetic current density of the catalyst sample at 0.1V vs.RHE was 3.7A / mg.

[0084] The following are comparative examples of the present invention.

[0085] Comparative Example 1

[0086] The difference from Example 1 is that the prepared catalyst does not contain yttrium and transition metal iron. The specific steps include:

[0087] 1) dissolving polyethylene glycol in water and stirring for 6 hours to form a 0.1 g / mL polymer solution; then adding the same amount of pure water solution not containing yttrium and iron salt as in step S1 of Example 1 and stirring for 2 hours to obtain a mixed solution;

[0088] 2) Dispersing zinc oxide nanoparticles with a size of 20 nm in a water solvent to prepare a dispersion, setting the mass ratio of zinc oxide to polymer to be 1:10, and adding the dispersion to the mixed solution of step 1), continuing ultrasonication and stirring for 1 hour; then placing in a freeze dryer for freeze drying to obtain a sample;

[0089] 3) The sample of step 2) was placed in a quartz boat and placed in an atmosphere furnace, and the temperature was raised to 900° C. at a rate of 1° C. / min and kept at that temperature for 1 h under the protection of argon gas with a flow rate of 10 mL / min, and then naturally cooled to room temperature and taken out to obtain a porous carrier containing a reinforcement phase;

[0090] 4) The porous carrier of step 3) is physically ground and dispersed in water, and a 0.1 g / L platinum nitrate solution with a mass ratio of platinum to polymer of 1:10 is added, and the mixture is fully contacted under nitrogen protection and dried at 40°C; then, the mixture is heated to 200°C at a heating rate of 1°C / min and kept warm for 0.5h under a flow rate of 10 mL / min of hydrogen / argon mixed gas for secondary heat treatment, and the mixture is naturally cooled to room temperature, taken out and fully physically ground to obtain a hydrogen adsorption catalyst.

[0091] By performing BET test on the catalyst, the specific surface area of ​​the hydrogen adsorption catalyst prepared in Comparative Example 1 is 977 m 2 / g, tested by electrochemical workstation and rotating disk electrode, the kinetic current density of the catalyst sample at 0.1V vs.RHE is 5.5A / mg.

[0092] Comparative Example 2

[0093] The difference from Example 1 is that the prepared catalyst does not contain transition metal iron. The specific steps include:

[0094] 1) dissolving polyethylene glycol in water and stirring for 6 hours to form a 0.1 g / mL polymer solution; then adding 0.01 mol / L yttrium bromide solution and an equal amount of pure water solution without iron salt as in Example 1, setting the mass ratio of yttrium element to polymer to 1:10, and stirring for 2 hours to obtain a mixed solution;

[0095] 2) Dispersing zinc oxide nanoparticles with a size of 20 nm in a water solvent to prepare a dispersion, setting the mass ratio of zinc oxide to polymer to be 1:10, and adding the dispersion to the mixed solution of step 1), continuing ultrasonication and stirring for 1 hour; then placing in a freeze dryer for freeze drying to obtain a sample;

[0096] 3) The sample of step 2) was placed in a quartz boat and placed in an atmosphere furnace, and the temperature was raised to 900° C. at a rate of 1° C. / min and kept at that temperature for 1 h under the protection of argon gas with a flow rate of 10 mL / min, and then naturally cooled to room temperature and taken out to obtain a porous carrier containing a reinforcement phase;

[0097] 4) The porous carrier of step 3) is physically ground and dispersed in water, and a 0.1 g / L platinum nitrate solution with a mass ratio of platinum to polymer of 1:10 is added, and the mixture is fully contacted under nitrogen protection and dried at 40°C; then, the mixture is heated to 200°C at a heating rate of 1°C / min and kept warm for 0.5h under a flow rate of 10 mL / min of hydrogen / argon mixed gas for secondary heat treatment, and the mixture is naturally cooled to room temperature, taken out and fully physically ground to obtain a hydrogen adsorption catalyst.

[0098] By performing BET test on the catalyst, the specific surface area of ​​the hydrogen adsorption catalyst prepared in Comparative Example 2 is 972 m 2 / g, tested by electrochemical workstation and rotating disk electrode, the kinetic current density of the catalyst sample at 0.1V vs.RHE is 8.1A / mg.

[0099] Comparative Example 3

[0100] The difference from Example 1 is that the prepared catalyst does not contain yttrium. The specific steps include:

[0101] 1) dissolving polyethylene glycol in water and stirring for 6 hours to form a 0.1 g / mL polymer solution; then adding 0.01 mol / L sodium ferrite solution and an equal amount of pure water solution without yttrium salt as in Example 1, with a mass ratio of transition metal element to polymer of 0.2:10, and stirring for 2 hours to obtain a mixed solution;

[0102] 2) Dispersing zinc oxide nanoparticles with a size of 20 nm in a water solvent to prepare a dispersion, setting the mass ratio of zinc oxide to polymer to be 1:10, and adding the dispersion to the mixed solution of step 1), continuing ultrasonication and stirring for 1 hour; then placing in a freeze dryer for freeze drying to obtain a sample;

[0103] 3) The sample of step 2) was placed in a quartz boat and placed in an atmosphere furnace, and the temperature was raised to 900° C. at a rate of 1° C. / min and kept at that temperature for 1 h under the protection of argon gas with a flow rate of 10 mL / min, and then naturally cooled to room temperature and taken out to obtain a porous carrier containing a reinforcement phase;

[0104] 4) The porous carrier of step 3) is physically ground and dispersed in water, and a 0.1 g / L platinum nitrate solution with a mass ratio of platinum to polymer of 1:10 is added, and the mixture is fully contacted under nitrogen protection and dried at 40°C; then, the mixture is heated to 200°C at a heating rate of 1°C / min and kept warm for 0.5h under a flow rate of 10 mL / min of hydrogen / argon mixed gas for secondary heat treatment, and the mixture is naturally cooled to room temperature, taken out and fully physically ground to obtain a hydrogen adsorption catalyst.

[0105] By performing BET test on the catalyst, the specific surface area of ​​the hydrogen adsorption catalyst prepared in Comparative Example 3 is 956 m 2 / g, tested by electrochemical workstation and rotating disk electrode, the kinetic current density of the catalyst sample at 0.1V vs.RHE is 7.4A / mg.

[0106] pass Figure 3 , and combined with the performance test results of Example 1 and Comparative Examples 1 to 3, it can be seen that the kinetic current density of Comparative Example 1 at 0.1V vs.RHE is lower than the values ​​of the catalysts containing only yttrium in Comparative Example 2 and only transition metal iron in Comparative Example 3, and is much lower than the values ​​of the catalyst containing both yttrium and transition metal iron in Example 1, which can explain: the rare earth yttrium component and the transition metal component and their simultaneous existence and mutual compounding have a positive enhancement effect on the catalyst. In addition, the kinetic current density of Comparative Example 2 at 0.1V vs.RHE is lower than the value of the catalyst in Example 1, indicating that the rare earth yttrium component plays a positive enhancement role in the performance of the catalyst when compounded with the transition metal; the kinetic current density of Comparative Example 3 at 0.1V vs.RHE is lower than the value of the catalyst in Example 1, indicating that the transition metal component plays a positive enhancement role in the performance of the catalyst when compounded with the rare earth yttrium.

[0107] In summary, the combination of rare earth yttrium component and transition metal component in the catalyst has a significant positive effect on the performance of the catalyst. This synergistic effect is not only reflected in the improvement of the catalyst performance when the two exist alone, but also in the significant performance gain brought about by their combined action.

[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrogen adsorption catalyst, characterized in that: The method comprises the following steps: S1. Under stirring conditions, preparing a polymer solution, and then sequentially adding an yttrium precursor solution and a transition metal precursor solution to obtain a mixed solution; S2, preparing a dispersion containing zinc oxide, adding the dispersion to the mixed solution of step S1, ultrasonicating, stirring, and freeze-drying to obtain a sample; S3, under the protection of an inert gas, heating the sample of step S2 and keeping it warm, and cooling it naturally to obtain a porous carrier; S4, grinding the porous carrier of step S3 and placing it in a solvent, adding a platinum precursor solution, drying it under the protection of an inert gas, and then heat treating it under a specific gas, and grinding it after natural cooling to obtain a hydrogen adsorption catalyst.

2. The preparation method according to claim 1, characterized in that In step S1, in the polymer solution, the polymer is selected from one or more of polyethylene glycol, polyvinyl pyrrolidone, polyacrylonitrile, polyimide, polyvinylidene fluoride or polyurethane; the solvent is selected from one or more of water, isopropanol, ethanol, acetone, dimethylformamide or N-methylpyrrolidone; and the concentration of the polymer solution is 0.1 to 1 g / ml.

3. The preparation method according to claim 1, characterized in that: The yttrium precursor is selected from one or more of yttrium bromide, yttrium chloride, yttrium nitrate, yttrium acetate, yttrium sulfate or yttrium acetylacetonate; the concentration of the yttrium precursor solution is 0.01-0.5 mol / L; In the transition metal precursor, the cation is sodium or potassium, and the anion is selected from one or more of ferrite, tetracarbonylferrite, cobalt cyanate, cobaltate, tetracarbonylcobaltate or nickel cyanate; the concentration of the transition metal precursor solution is 0.01-0.5 mol / L.

4. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the yttrium element in the yttrium precursor, the transition metal cation and the polymer is 1:(0.2-5):(10-1000).

5. The preparation method according to claim 1, characterized in that: In step S2, the particle size of the zinc oxide is 20-100 nm; the mass ratio of the zinc oxide to the polymer is 1:(10-50).

6. The preparation method according to claim 1, characterized in that: The inert gas is selected from argon or nitrogen, and the gas flow rate is 10-200 ml / min.

7. The preparation method according to claim 1, characterized in that: In step S3, the heating method is: heating to 200-900°C at a rate of 1-10°C / min.

8. The preparation method according to claim 1, characterized in that: In step S4, the platinum precursor is selected from one of platinum nitrate, platinum perchlorate or platinum acetylacetonate; the concentration of the platinum precursor solution is 0.1-5 g / L; the mass ratio of the platinum element in the platinum precursor to the polymer is 1:(10-500).

9. The preparation method according to claim 1, characterized in that: In step S4, the specific gas is hydrogen and / or argon, and the gas flow rate is 10-50 mL / min; the heat treatment method is: heating to 200-900° C. at a rate of 1-5° C. / min and keeping warm.

10. A hydrogen adsorption catalyst prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The specific surface area of ​​the hydrogen adsorption catalyst is 400m 2 / g, and the kinetic current density at 0.1V vs.RHE exceeds 5A / mg.

Citation Information

Patent Citations

  • Pt alloys with high HOR catalytic activity, their preparation methods and applications

    CN111554946B

  • Pd-X modified X element doped mesoporous carbon hydrogen storage and hydrogen oxidation catalyst dual-functional material and preparation method and application thereof

    CN115872355B

  • PdNi-C composite material catalyst as well as preparation method and application thereof

    CN117976925A